The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1159/000506103
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo: A Review

Abstract: Vitiligo, a common depigmenting skin disorder, has an estimated prevalence of 0.5-2% of the population worldwide. The disease is characterized by the selective loss of melanocytes which results in typical nonscaly, chalky-white macules. In recent years, considerable progress has been made in our understanding of the pathogenesis of vitiligo which is now clearly classified as an autoimmune disease. Vitiligo is often dismissed as a cosmetic problem, although its effects can be psychologically devastating, often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
632
3
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 458 publications
(660 citation statements)
references
References 265 publications
(426 reference statements)
3
632
3
22
Order By: Relevance
“…This is in contrast with the general opinion that vitiligous patches featuring leukotrichia on clinical ground are associated with a lack of therapeutic response due to a possible reduction/absence of follicle-associated melanocytes in white hairs [1][2][3][4][5][6][7][8]. However, the speculated association between leukotrichia and poor therapeutic response is mainly based on studies on segmental vitiligo [27,28], which is notoriously more resistant to treatments compared with NSV [1][2][3][4][5][6][7][8]. Additionally, some studies showed that it is still possible to find follicleassociated melanocytic precursors in white hairs, which if stimulated, might migrate and differentiate, thereby giving rise to pigment production [29,30].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This is in contrast with the general opinion that vitiligous patches featuring leukotrichia on clinical ground are associated with a lack of therapeutic response due to a possible reduction/absence of follicle-associated melanocytes in white hairs [1][2][3][4][5][6][7][8]. However, the speculated association between leukotrichia and poor therapeutic response is mainly based on studies on segmental vitiligo [27,28], which is notoriously more resistant to treatments compared with NSV [1][2][3][4][5][6][7][8]. Additionally, some studies showed that it is still possible to find follicleassociated melanocytic precursors in white hairs, which if stimulated, might migrate and differentiate, thereby giving rise to pigment production [29,30].…”
Section: Discussionmentioning
confidence: 72%
“…Narrowband ultraviolet B (Nb-UVB) therapy (wavelength ranging from 311 to 313 nm) is one of the most prescribed treatments for NSV, with variable therapeutic results being reported in daily clinical practice [7]. According to literature data, several factors may negatively affect the outcome of Nb-UVB therapy in NSV, including disease activity, associated autoimmune diseases, extensive involvement, family history of vitiligo, long duration of disease, mucosal involvement, presence of koebnerization and leukotrichia [1][2][3][4][5][6][7][8]. However, darker phototypes, early therapeutic response, and facial involvement are associated with a good treatment outcome [9].…”
Section: Introductionmentioning
confidence: 99%
“…Generalized vitiligo was diagnosed by dermatologists at General hospital, using Wood's lamp as bilateral, symmetrical, depigmented macules or patches occurring in a random distribution over the entire body surface. [1] The extent of vitiligo depigmentation was measured by vitiligo area severity index (VASI) score. [19] As described by Bhor and Pande, [19] the total body VASI score for GV patients was calculated as the product of the vitiligo area and the degree of the depigmentation within each patch determined by the hand units and a hand unit is approximately 1% of the total body surface area.…”
Section: Patients and Controlsmentioning
confidence: 99%
“…Generalized vitiligo (GV) is an acquired and polygenic skin depigmenting disease characterized by bilateral, symmetrical depigmented patches over the entire body. [1] GV has been suggested to be caused due to autoimmune-mediated loss of functional melanocytes. [2] About 0.5%-2% population worldwide is affected with vitiligo.…”
Section: Introductionmentioning
confidence: 99%
“…Vitiligo is a disease characterized by the loss of melanin pigment in one or more circumscribed areas of the skin [1] . The term is derived from the Latin word "vitellus" meaning veal, in reference to the paleness of the skin.…”
Section: Introductionmentioning
confidence: 99%